Risk factors and the surgery affection of respiratory complication and its mortality after acute traumatic cervical spinal cord injury. Issue 36 (September 2017) - Yang, Xiao-xiong; Huang, Zong-qiang; Li, Zhong-hai; Ren, Dong-feng; Tang, Jia-guang
Abstract : Abstract: The aim of this study is to estimate the risk factors of both respiratory complication (RC) and mortality after acute traumatic cervical spinal cord injury (TCSCI). Between July 2005 and July 2015, in 181 patients (142 males and 39 females; mean age 41.0 years) with acute TCSCI, we compared the difference and odds ratio in RC group (n = 73) with that of non-RC group (n = 108), and also death group (n = 15) and survival group (n = 166). We collected injury-related information after half a year of injury, which is as follows: the causes of injury, time of surgery, ICU (intensive care unit) days, ventilator days, ASIA (American Spinal Injury Association) classification, neurological injury, CIPS (Clinical Pulmonary Infection Score), and BMI (body mass index). Besides these, we gathered the general information such as age, gender, smoking history, and use of steroids. The study compared perioperative parameters; surgery-related and instrumentation- and graft-related complication rates; clinical parameters; patient satisfaction; and radiologic parameters. Variations like gender (odds ratio [OR] = 1.269, 95% confidence interval [CI] [0.609–2.646]), smoking history (OR = 2.902, 95% CI [1.564–5.385]), AIS grade (grade A) (OR = 6.439, 95% CI [3.334–12.434]), neurological level (C1-C4) (OR = 2.714, 95% CI [1.458–5.066]), and steroid use (OR = 2.983, 95% CI [1.276–6.969]) have a facilitated effect on RC. When we estimated surgery-related affection, only the time of surgery and anterior approach compared with posterior has significant difference in RC ( P  < .05). Between death and survival group, the aspect of age, non-surgical, CPIS, AIS grade, and BMI have statistically significant difference. Survival analysis reveals significant difference in aforementioned groups. In patients suffering from acute TCSCI, those who are old, have long smoking history, complete spinal cord injury, C1-C4, high CPIS, and fat have high incidence of RC and mortality.